The Effect Of Work-Life Balance And Rewards On Turnover Intention Of Solaria Bengkulu Employees - Iklas Ade Putra; Ida Ayu Er Meytha Gayatri; M. Rahman Febliansa (Utami Publisher, 2026)
The purpose of this study was to determine the effect of work-life balance and rewards on turnover intention among Solaria Bengkulu employees. This quantitative research employed a survey method and a questionnaire as the instrument. The results of the regression analysis showed Y = 55.451 - 0.208X1 - 0.347X2, indicating that Work-Life Balance (X1) and Rewards (X2) negatively influence Turnover Intention (Y). Improving Work-Life Balance and providing positive rewards can reduce employees' desire to leave the company. The coefficient of determination was 49.3%. This means that work-life balance and rewards contribute 49.3% to turnover intention, while other variables not examined in the study influence the remaining 50.7%. The t-test results at a significance level of 0.05 indicate that Work-Life Balance and Rewards partially significantly influence Turnover Intention among Solaria Bengkulu employees. The results of the F test at a significance level of 0.05 explain that the Work-Life Balance and Reward variables have a significant influence on the Turnover Intention variable for Solaria employees in Bengkulu.